2011
DOI: 10.1097/prs.0b013e3182174278
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Sham-Controlled Trial to Evaluate the Safety and Effectiveness of a High-Intensity Focused Ultrasound Device for Noninvasive Body Sculpting

Abstract: Therapeutic, II.(Figure is included in full-text article.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
88
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 12 publications
2
88
0
4
Order By: Relevance
“…The focused ultrasound devices have been well studied by Kennedy et al, 20 who noted that the thermal effects of the applied ultrasound energy resulted in fat cell necrosis within the treatment area. Jewell et al, 21 as well as Fatemi and Kane, 22 reported significant reductions in waist circumference in their subjects following focused ultrasound treatments.…”
mentioning
confidence: 97%
“…The focused ultrasound devices have been well studied by Kennedy et al, 20 who noted that the thermal effects of the applied ultrasound energy resulted in fat cell necrosis within the treatment area. Jewell et al, 21 as well as Fatemi and Kane, 22 reported significant reductions in waist circumference in their subjects following focused ultrasound treatments.…”
mentioning
confidence: 97%
“…Em quantidades elevadas, essas lipoproteínas aumentam o risco de desenvolvimento da doença aterosclerótica 3 . Poucos foram os estudos que avaliaram o impacto deste procedimento no perfil lipídico [11][12][13][14][15][16] . Apenas Moreno-Moraga et al 11 demonstraram ligeiro aumento dos TG plasmáticos em ambos os gêneros mesmo não havendo sobrecarga hepática na imagem ultrassonográfica.…”
Section: Discussionunclassified
“…Aventa-se a ideia de que isto possa desencadear um processo inflamatório. De fato, semelhante ao processo fisiológico, após o dano tecidual os adipócitos sofrem apoptose e desencadeiam uma resposta inflamatória composta por macrófagos e neutrófilos que fagocitam as células danificadas, além da liberação de citocinas importantes 7,16,21 . Aventa-se a ideia de que isto poderia favorecer um processo inflamatório de caráter sistêmico, aumentando o risco para o desenvolvimento de algumas condições clínicas não favoráveis.…”
Section: Discussionunclassified
“…In mehreren kontrollierten Studien konnte gezeigt werden, dass die Methode wirksam und bei richtiger Anwendung auch sicher ist [16,17]. Nach 1-maliger Anwendung wurde eine durchschnittliche Reduzierung des Bauchumfangs um 2,5 cm beobachtet.…”
Section: Introductionunclassified